Taxation in Western Europe, 1963 : a guide for industrialists - Federation of British Industries (London : Federation of British Industries, 1963)
This edition includes information additional to that contained in the 1962 edition and deals with specific changes made in the tax systems of various countries, particularly the major reform in Belgium.
Formerly 'Taxation in the proposed European Free Trade Area'
oif 29/01/2019
Ref.
Keywords: Taxation; European Economic Community; International economic integration; Europe; Europe, Western